Modified fracture properties of cement composites with nano/micro carbonized bagasse fibers - Rao Arsalan Khushnood; Sajjad Ahmad; Giuseppe Andrea Ferro; Luciana Restuccia; Jean Marc Tulliani; Pravin Jagdale (Fracture and Structural Integrity)
A novel cost-effective alternative in the form of nano/micro carbonized particles produced from waste bagasse fibers has been explored to modify the mechanical properties and fracture pattern of the resulting cementitious composites. Carbonized bagasse particles were produced at Politecnico di Torino and characterized by Raman spectroscopy and scanning electron microscopy. When added with cement paste up to 1 wt% in six different proportions, the carbonized bagasse particles were found effective in significant enhancement of mechanical strength as well as fracture toughness. From micro-graphical observations it is evident that these heterogenic inclusions either block the propagation of micro cracks which has to deviate from its straight trajectory and has to follow the carbon nano/micro particles contour or distribute it into multiple finer cracks. Crack contouring along the carbonized particle, crack pinning, crack diversions and crack branching are the mechanisms which can explain the increase of toughness in the composite samples